EVALUASI KEBIJAKAN PENGELOLAAN AIR TANAH DAN PERANNYA TERHADAP UPAYA KONSERVASI AIR TANAH DI KABUPATEN BANYUMAS - , JOKO NOVA ARIANTO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
One source of water is groundwater. Along with the increasing rate of population growth and development activities, the utilization of ground water for such needs have also increased. But on the other hand, the availability of ground water is decreasing if the management of these resources are not managed wisely. Groundwater Management is based on Groundwater Basin that organized based on ground water management policy with the principle of a balance between conservation and utilization of ground water. As a concrete manifestation of the community in supporting conservation efforts with the implementation of ground water is ground water tax, which is one aspect in the management of ground water. This study aimed to evaluate policy implementation of Local Regulation No. 22 Year 2011 about Groundwater and Local Regulation No. 1 Year 2011 about Local Taxes in particular Groundwater Tax, and analyze how the management of ground water and its role on the conservation of ground water in Banyumas. This study is about evaluation study by using formative evaluation approach. Which is to evaluate government programs or policies that are running. In this study will be evaluated and described the condition of groundwater management in generally in accordance with Local Regulation No. 22 Year 2011 , more particularly the implementation of policies related to groundwater conservation and evaluation of the implementation of the groundwater tax policy in accordance with Local Regulation No.1 Year 2011 on local taxes . Further evaluation of the extent of the groundwater management policies can support the conservation efforts undertaken by the Government of Banyumas. The results showed that the implementation of the Local Regulation No. 22 Year 2011 has yet to reach the expected goals, even the content in the licensing sector still cause confusion. This policy is also ineffective due to lack of human resources so that monitoring and control not be optimal. From the implementation of the Local Regulation No. 1 Year 2011 , there is the disadvantage that not all of the groundwater tax potential has unearthed and not used of water meter as a counter for the volume of water used. It can be concluded that groundwater management policies implemented including ground water tax collection does not have a significant role to the conservation of ground water in Banyumas. From the results of these studies can be proposed recommendation that Banyumas regency can address the problem by increasing the shortage of human resources in terms of both quantity and quality and can be re-reviewing the provisions are still ambiguous, which can be done for a change.